Parasites of Astyanax lacustris (Pisces, Characiformes) from Brazilian streams - Miguel, Bianca da Silva [UNESP]; Ramos, Igor Paiva [UNESP]; Zago, Aline Cristina [UNESP]; Delariva, Rosilene Luciana; Franceschini, Lidiane [UNESP] (FapUNIFESP (SciELO), 2024)
Astyanax lacustris is a small characid fish widely distributed in Brazil, with fast-growing and omnivorous feeding habits. Although the species presents economic and ecological importance, little is known about its parasitological fauna in stream environments. This study aimed to characterize the parasitic fauna of A. lacustris in two streams in the state of Paraná, Brazil. Fifty-two specimens of A. lacustris were collected, 22 from the Carolina stream (Lower Iguaçu River) and 30 from the Carreira stream (Upper Paraná River), in July and September 2018. In both streams, there was a low richness of parasites, and the structure of the parasitic community was predominantly composed of monogeneans. These findings may be associated with the gregarious behavior of the host species. Moreover, the low occurrence of endohelminths, may be associated with the fact that in streams, the energy flow is low, and depends directly on the input of allochthonous matter, which favors the formation of shelters for the establishment of macroinvertebrates, which represent important sources of food for the ichthyofauna, and may act as intermediate and paratenic hosts of parasites. These environments require further studies to support conservation measures aimed at maintaining the balance of ecological relationships in these preserved ecosystems.
Parasitas de Astyanax lacustris (Pisces, Characiformes) de riachos brasileiros
Keywords: fish of stream; ichtioparasitology; Monogenea; Nematoda; Yellow-tailed tetra